Language Sustainability in a Changing World - Burada, Marinela (Cambridge Scholars Publisher, 2020)
This volume includes thirteen papers presented at the 16th Conference on British and American Studies held at Transilvania University of Brașov, Romania. It consists of three main parts, the first of which includes contributions falling within the scope of communication and meaning-making. The articles gathered here consider issues such as social identity and the construction of gender both in and through language, and the rendition of cultural content across languages. The second section takes a closer look at language in context: the contributions included here approach language as a means t.